2019
DOI: 10.1002/hed.25564
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer PEG site metastases: Association with PEG placement method

Abstract: Background Many patients with head and neck cancer (HNC) will require feeding tube placement for nutritional support using percutaneous endoscopic gastrostomy (PEG) tube. Rarely, HNC metastases have been reported at the PEG site, a morbidity associated with a poor outcome. Methods Along with a case report, an evaluation of PEG placement methods with metastases from the literature was completed along with a statistical analysis of the literature to determine PEG site metastases and method of placement correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…Poor nutrition has been linked with adverse outcomes in the HNSCC patients’ population, hence alternative nutritional support means have understandably been employed to improve life expectancy and overall outcome [ 3 ]. Moreover, the global benefits of enteral nutritional support have become well-established as an adjunctive component in the interdisciplinary management of primary HNSCC [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor nutrition has been linked with adverse outcomes in the HNSCC patients’ population, hence alternative nutritional support means have understandably been employed to improve life expectancy and overall outcome [ 3 ]. Moreover, the global benefits of enteral nutritional support have become well-established as an adjunctive component in the interdisciplinary management of primary HNSCC [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEG site metastasis from primary HNSCCs is a rare but serious clinical entity [ 3 , 8 , 9 ]. According to a recent systematic review conducted by Siu et al in 2019 [ 8 ], a total of 121 cases of PEG site metastasis from various primary upper aerodigestive cancers were documented [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is also why the ESGE guidelines recommend the “push” technique in patients with HNC cancer 7 . However, a review of 62 case reports of PEG site metastasis showed that metastasis could occur even after introducer PEG placement 20 . Further studies are needed to gain a fuller understanding of HNC tumor seeding to gastrostomies.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, a review of 62 case reports of PEG site metastasis showed that metastasis could occur even after introducer PEG placement. 20 Further studies are needed to gain a fuller understanding of HNC tumor seeding to gastrostomies. The high number of patients and procedures included in the analysis represent important strengths of the study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Different methods of PEG placement do not differ significantly in the incidence of development of abdominal wall metastasis. 8 A study evaluating…”
Section: Descriptionmentioning
confidence: 99%